Talk is cheap?! The value of a ban on product simulations and renderings on a crowdfunding platform. Issue 44 (20th September 2021) - Patel, Pankaj C.; Wolfe, Marcus T.; Manikas, Andrew S
ABSTRACT: We exploit the 20 September 2012 intervention on Kickstarter where projects in the Hardware and Project Design categories, but not in other categories, were prohibited from presenting simulations and renderings in their crowdfunding campaigns. Using a partition-type analysis estimate for 110, 258 projects, we find that the intervention lowered the odds of meeting the funding goal (extensive margin); however, it did not significantly increase the amount of funding received above the goal amount (intensive margin). The findings are robust to pre-trends tests. Post-intervention, based on the exploration-exploitation framework, projects in the treated categories used more exploitative (vs. explorative) language. Furthermore, projects in the treated category benefited from using narcissistic and entrepreneurial orientation rhetoric before the intervention; however, this did not hold after the intervention. Finally, projects from the control categories did not increase deceptive language after the intervention and experienced lower odds of meeting funding goals after the intervention when using ambiguous language. The findings highlight the role of centralized intervention in improving signals on noisy crowdfunding platforms and the declining role of rhetoric for both treated and control categories.